Platelet-to-lymphocyte ratio as a potential prognostic factor in nasopharyngeal carcinoma: A meta-analysis. Issue 38 (September 2019) - Cen, Rui-Xiang; Li, Yu-Gang
Abstract: Background: The aim of this study was to investigate the use of pretreatment platelet-to-lymphocyte ratio (PLR) as a prognostic marker in patients with nasopharyngeal carcinoma (NPC). Methods: A literature search was conducted using online databases such as MEDLINE, EMBASE, Cochrane Library, and WangFang. Overall survival (OS), progression-free survival (PFS), and clinicopathological features were generated and compared. Results: Ten studies that included 3388 patients were analyzed in this meta-analysis. Among them, 8 studies with 3033 patients with NPC investigated the prognostic role of PLR for OS and showed that elevated PLR was associated with poor OS (HR: 1.77, 95% CI: 1.46–2.15, P  < .001). Five studies that included 1156 patients investigated the role of PLR in predicting PFS, and showed that high PLR was associated with poor PFS (HR: 1.65, 95% CI: 1.26–2.17, P  < .001). Moreover, high PLR correlated with the N stage (N2-3 vs N0-1; OR: 1.55, 95% CI: 1.02–2.34, P  = .04). Conclusion: Our study suggested that high PLR is associated with worse prognosis in patients with NPC. Pretreatment PLR could serve as a simple, promising indicator for prognostic evaluation in patients with NPC.